2016
DOI: 10.1111/and.12544
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of traditional Chinese medicine on pain and inflammation in chronic nonbacterial prostatitis in rats

Abstract: According to traditional Chinese medicine, the symptoms of chronic nonbacterial prostatitis/chronic pelvic pain syndrome (CNP/CPPS) may be treated using a cocktail of herbs that stimulate blood circulation ('activating blood circulation formula'). We investigated the effect of three doses of this formula on a rat model of CNP/CPPS. Male Wistar rats were injected with a saline extract of male sex accessory glands on days 0 and 30 to induce prostatitis and then treated daily by gavage between days 32 and 60. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Prostatitis, a general term describing prostate inflammation, is a common disease that could be sustained by bacterial or non-bacterial infectious agents [ 1 ]. Considering the inflammatory pathways involved in prostatitis, the efficacy of herbal extracts endowed with antioxidant and anti-inflammatory effects for reducing the burden of inflammation and oxidative stress, with possible improvements in clinical symptoms [ 2 , 3 ], is under investigation. Pollen extract has been previously reported as a promising natural product in managing clinical symptoms related to prostatitis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prostatitis, a general term describing prostate inflammation, is a common disease that could be sustained by bacterial or non-bacterial infectious agents [ 1 ]. Considering the inflammatory pathways involved in prostatitis, the efficacy of herbal extracts endowed with antioxidant and anti-inflammatory effects for reducing the burden of inflammation and oxidative stress, with possible improvements in clinical symptoms [ 2 , 3 ], is under investigation. Pollen extract has been previously reported as a promising natural product in managing clinical symptoms related to prostatitis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The H. diffusa Willd aqueous extraction was prepared according to the traditional Chinese decoction method (Cui et al, 2020;Liu et al, 2016). The H. diffusa Willd herb (60 g) was kept in the arenaceous boiler and soaked for 1 hr in 8 volumes of cold water before boiling.…”
Section: Preparation and Administration Of H Diffusa Willd Aqueousmentioning
confidence: 99%
“…Yin deficiency and damp-heat, qi stagnation and blood stasis are the main pathogenic factors. By applying the unique diagnosis and treatment system of TCM to treat prostatitis, the clinical effect is remarkable (9). Recent studies have shown that the effective active ingredients in TCM can improve the blood supply of peripheral blood vessels and achieve the purpose of treatment (10).…”
Section: Introductionmentioning
confidence: 99%